Colonial Diplomatic Relations and the Development of Pearling Industry in the Netherlands Indies, 1894-1899 - Rasyid, Rangga Ardia (Jurnal Sejarah Citra Lekha, 2024)
The pearling industry that developed in the Netherlands East Indies (now Indonesia) had a particularly Australian character. This influence was especially pronounced during the time of James Clark and his Celebes Trading Company (CTC) consortium (1905-1918), which operated primarily in the Aru Islands of the southeastern Moluccas. However, even before the CTC, Anglospheric influence was evident in the Ordinances passed by the Dutch colonial government throughout the late 19th and early 20th centuries. While discussions of transnational elements in pearling history have often focused on Australian capitalist expansion or pearling crew movements, often overlooked aspect is the role of colonial government policy. Therefore, this research primarily utilizes the abundant colonial archives housed in the Indonesian National Archive (ANRI) in Jakarta, focusing on documents related to the drafting of pearling ordinances. Additionally, Australian and Dutch newspaper archives obtained from online sites are also consulted. By examining these sources, this article highlights the use of colonial diplomatic networks in formulating a new pearling industry, particularly the correspondence between Dutch and British colonial officials. It also aims to understand how these diplomatic networks influenced the growth of the pearling business in the Netherlands East Indies. This research concludes that transnational forces played a significant role in shaping the legal structure of the Netherlands East Indies pearling industry. It demonstrates that the Dutch colonial state was not simply a passive actor reacting to external threats. Instead, it actively participated in creating the legal framework for pearl fishing in the region.